Correlation of Makrozoobenthos Distribution And Aquatic Condition On Sei Barombang’s Mangrove Ecosystem, Labuhan Batu District, North of Sumatera - Rivo Hasper Dimenta; Rusdi Machrizal; Karunia Safitri; Khairul Khairul (Universitas Gorontalo, 2020)
Macrozoobethos an animal whose part or all of their life cycle at bottom of water and very sensitive to changes in the aquatic environment. so that they are often used as bioindicators of water quality. The research was conducted to determine the distribution and diversity of macrozoobenthos in Sei Barombang’s mangrove ecosystem, and to know the correlation between of diversity of macrozoobenthos with the parameters of physic-chemical water). Determination of observation stations using purposive sampling method. Macrozoobenthos was collected using by handsortir method from 3 station, first station on Nypa frutican vegetation, second station on Sonneratia sp. vegetation, and third station on heterogeneous mangrove vegetation. Measurement of physical-chemical parameters such as temperature, salinity, pH and dissolved oxygen (DO) of water. The data analysis, such as index of diversity (Shannon-Wiener index-H’), the Similarity index (by Evannes index), index dominance of species (by Simpson Index), Pearson’s correlation used for 2 factors among diversity and the physical-chemical parameters by SPSS 22. Result showed were gastropod and bivalvia as dominant species from amount of 11 species of macrozoobenthos found in Sei Barombang mangrove ecosystem, where Barbatia amygdalumtosum as lowest species found, Glauconome virens and Pleurocera canaliculate as the most species often found in all station. And The results of Pearson correlation analysis showed that dissolved of oxygen (DO) (0.776) and water pH (0.656) be determinant of the distribution of diversity macrozoobenthos in the location of research